Modul Edukasi Online terhadap Peningkatan Pengetahuan Kader dalam Deteksi Stunting di Wilayah Kerja Puskesmas Singkawang Utara 1 - Marsia Marsia; Erni Juniartati; Dwi Sulistyawati (Jurnal Ners, 2026)
Stunting remains a major public health issue characterized by chronic malnutrition that affects children’s physical growth, cognitive abilities, and long-term productivity. Limited knowledge and skills among community health cadres in conducting early detection contribute to the persistence of stunting cases in Indonesia. This study aimed to evaluate the effectiveness of an educational module in improving cadres’ knowledge regarding stunting detection in the working area of Puskesmas Singkawang Utara 1. A quasi-experimental design using a pretest–posttest with control group approach was employed. A total of 63 cadres were selected through total sampling and assigned to an intervention group receiving an online educational module and a control group receiving a printed module. Knowledge was assessed before and after the intervention using a structured questionnaire. Normality testing revealed non-normally distributed data; thus, the Wilcoxon test was applied. Results showed a significant increase in knowledge scores from 38.65 to 77.14 after the intervention (p = 0.000). These findings indicate that the educational module, particularly in online form, is effective in enhancing cadres’ understanding of stunting detection and can be integrated into community-based stunting prevention programs..